Re-evaluation of the age of some dinosaur localities from the southern Pyrenees by means of megaloolithid oospecies - Vila, B.; Sellés, A.G. (Journal of Iberian Geology, 2015)
Since the beginning of the 20th Century the Upper Cretaceous continental and transitional marine deposits of the southern Pyrenees have produced more than 220 dinosaur fossil localities. New discoveries and advances in magnestostratigraphy and biostratigraphy provide a robust biostratigraphical framework for the latest Cretaceous dinosaur faunas in the region, although the age of some localities has remained uncertain. Here, we re-evaluate the age of some classic and new dinosaur fossil localities on the basis of the potential dating of megaloolithid oospecies and provide parataxonomic and age data for twenty-three localities with new megaloolithid egg fossils. Further, we review the nomenclature and probable synonymies of several of the most historically significant localities in the southern Pyrenees. With the new age assignments proposed for some significant localities (Basturs, Orcau-1, Els Nerets, Figuerola-2, Suterranya-1), we claim that in the southern Pyrenees a) the ankylosaurian dinosaurs survived beyond the early Maastrichtian-late Maastrichtian boundary and coexisted with hadrosauroids; b) the theropod record is scarce in the early Maastrichtian and the taxonomic diversity (richness) of theropods is notably higher in the late Maastrichtian; and c) the megaloolithid egg record assigned to sauropods is continuous through the entire Maaastrichtian but is scarce in the Upper Campanian.